Volume 1: Advances in Aerospace Technology 2010
DOI: 10.1115/imece2010-38603
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into the Feasibility of an Augmented Propeller Design With the Use of a Passive Circulation Control System

Abstract: Circulation control is a high-lift methodology that can be used in a variety of fluid dynamic systems, such as, on the wing of an aircraft. Circulation control increases the near surface velocity of the airflow over a rounded surface of an object, typically a slightly modified airfoil. This is primarily achieved though the addition of a jet of air to a specially designed aircraft wing using a series of blowing slots that eject pressurized high velocity (above the free-stream velocity) jets of air over the trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Preliminary research has been done at WVU with respect to the feasibility of adding a passively pressurized circulation control slot to a propeller body, for implementation to already existing UAV aircraft [24]. This previous work showed that the use of a rounded trailing edge and circulation control plenum/ejection slot at specifically designed and located areas on a propeller blade could potentially provide a single digit performance increase in thrust of the propeller, thus increasing the overall efficiency and fuel economy of the aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary research has been done at WVU with respect to the feasibility of adding a passively pressurized circulation control slot to a propeller body, for implementation to already existing UAV aircraft [24]. This previous work showed that the use of a rounded trailing edge and circulation control plenum/ejection slot at specifically designed and located areas on a propeller blade could potentially provide a single digit performance increase in thrust of the propeller, thus increasing the overall efficiency and fuel economy of the aircraft.…”
Section: Introductionmentioning
confidence: 99%